2001
DOI: 10.1007/s002800100370
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine activity in cervical cancer cell lines

Abstract: We recommend performing additional in vitro experimentation so that these results can be confirmed to support clinical trials of gemcitabine in cervical cancer patients both as first-line therapy and with concomitant radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Clonogenic assays were performed as reported previously. 27 The analyses were performed at least in triplicate in four independent experiments. Nuclear staining.…”
Section: Methodsmentioning
confidence: 99%
“…Clonogenic assays were performed as reported previously. 27 The analyses were performed at least in triplicate in four independent experiments. Nuclear staining.…”
Section: Methodsmentioning
confidence: 99%
“…Gemcitabine which is used in study arm has been shown to be a potent Radiosensitizer in cervical cell line (7) . Gemcitabine has shown promising radio sensitising effect in preclinical as well as in clinical phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is a known radiosensitizer and has been used in a wide variety of human cancer cell lines (6) . Various studies have reported that Gemcitabine is highly synergistic to radiation in cervical cancer cell lines (7) . Several trials were performed with Gemcitabine as radiosensitiser (8,9) .…”
Section: Jmscr Vol||05||issue||07||page 25734-25742||julymentioning
confidence: 99%
“…Hernandez et al 14 have demonstrated the radiosensitizing effect of gemcitabine against cervical cancer cell line. Overall toxicity was acceptable and tolerable.…”
Section: Discussionmentioning
confidence: 99%